Quantifying Nature in Tourism Discourse: A Corpus-ecolinguistic Perspective - Isti'anah, Arina; Suhandano, Suhandano; Winarti, Daru (Masyarakat Linguistik Indonesia Universitas Andalas, 2024)
Nature or the physical environment is strategically presented as a compelling attraction to persuade tourists to visit a country, including Indonesia. While previous studies investigated tourism promotion from persuasive devices like metaphors and adjectives, this study takes a different trajectory by investigating the language of attitudes, identified explicitly from the Graduation, in tourism promotion discourse. This study built a specific corpus compiled from articles promoting nature on the official website of Indonesian tourism (OWIT). Using Sketch Engine and Wmatrix5, this study aims to identify 1) the types of nature offered on the Indonesian tourism promotion website, 2) quantification and its grammatical realization used in the promotion, and 3) attitudes amplified from the graduation strategy. Findings reveal that Indonesian tourism is promoted mainly by its topography, flora and fauna, nature-based activity, and weather and climate. Graduation is realized through diverse grammatical realizations, such as the specific and non-specific numerals and infused amounts, in order to quantify nature’s values/ numbers, extent, and mass/ presence. The concordance study indicates that upscaling quantification emphasizes Indonesia’s natural beauty and richness, while downscaling quantification promotes the endangered species in Indonesia’s national parks. From an ecological lens, the Graduation is employed to amplify readers’ Appreciation of the country’s valuation and composition. Quantification has also been proven to be a productive persuasive device in tourism promotion that functions to materialize and commodify nature. Notwithstanding the corpus size, this study contributes to tourism promotion discourse and ecolinguistics studies.